The role of artificial intelligence in improving the protection of researchers’ rights in the procedure of election to academic titles - Čović, Ana (Sociološki pregled, 2025)
In October 2024, the Rulebook on the Acquisition of Academic Titles (“Official Gazette of the RS”, 80/2024) came into force, and it is to be applied from 1 June 2025 instead of the currently applicable Rulebook on the Acquisition of Academic Titles (“Official Gazette of RS”, 159/20 and 14/23). The first part of this article will provide an overview of the first-degree procedure of election to an academic title, and then it will also present a case study of the second-degree procedure before the National Council for Scientific and Technological Development as initiated by means of appeal (in this case study, the appeal was lodged by the author herself). In structuring her work like this, the author hopes that her experiences and the lessons she learned from them will be of use to researchers in some future procedures. In the second part of the article, the author will try to answer two questions. The first question to be addressed is whether certain situations are recognized as being defined with enough precision, or whether the existing options have been kept, leaving the possibility for discretional interpretation. The second question to be addressed concerns the ways in which the established system of eNauka (eScience) and the possibilities offered by artificial intelligence can be used for improving the protection of researchers’ rights in their procedures of election to academic titles, and, ipse facto, for improving science policies in the Republic of Serbia. Specifically, in this respect, the possibility of introducing personal assistants in the form of AI avatars is suggested.
Keywords: eNauka; artificial intelligence; researchers’ rights; main scientific boards; Commission for the Acquisition of Academic Titles; Rulebook on the Acquisition of Academic Titles; National Council for Scientific and Technological Development